Adipose tissue‐specific modulation of galectin expression in lean and obese mice: Evidence for regulatory function12. (26th March 2013) - Rhodes, Davina H.; Pini, Maria; Castellanos, Karla J.; Montero‐Melendez, Trinidad; Cooper, Dianne; Perretti, Mauro; Fantuzzi, Giamila
Abstract Objective: Galectins (Gal) exert many activities, including regulation of inflammation and adipogenesis. We evaluated modulation of Gal‐1, ‐3, ‐9 and ‐12 in visceral (VAT) and subcutaneous (SAT) adipose tissue in mice. Design and Methods: We used two mouse models of obesity, high‐fat diet induced obesity (DIO) and ob/ob mice. We also evaluated the response of Gal‐1 KO mice to DIO. Results: Both age and diet modulated expression of galectins, with DIO mice having higher serum Gal‐1 and Gal‐3 versus lean mice after 13‐17 weeks of high‐fat diet. In DIO mice there was a progressive increase in expression of Gal‐1 and Gal‐9 in SAT, whereas Gal‐3 increased in both VAT and SAT. Expression of Gal‐12 declined over time in VAT of DIO mice, similar to adiponectin. Obesity lead to increased production of Gal‐1 in adipocytes, whereas the increased Gal‐3 and Gal‐9 of obesity mostly derived from the stromovascular fraction. Expression of Gal‐12 was restricted to adipocytes. There was increased production of Gal‐3 and Gal‐9, but not Gal‐1, in CD11c− and CD11c+ macrophages from VAT of DIO versus lean mice. Expression of Gal‐1, ‐3 and ‐12 in VAT and SAT of ob/ob mice followed a trend comparable to DIO mice. Rosiglitazone reduced serum Gal‐1, but not Gal‐3 and modulated expression of Gal‐3 in VAT and Gal‐9 and Gal‐12 in SAT of DIO mice. High‐fat feeding lead to increased adiposity in Gal‐1 KO versus WT mice, with loss of correlation between leptin and adiposity and no alterations in glucose and insulin levels. Conclusions: Obesity leads to differential modulation of Gal‐1, 3, 9 and 12 in VAT and SAT, with Gal‐1 acting as a modulator of adiposity.